(3OQGSI ejOGfjI HGdeDSSI GdYehejI GdLRGFQjI ddCfSLI GdUfGYjI (B- (3GdeSjdIs - (3eUWai (B, (3HhLdGds ((3YeGf(B:s (3eQcR GdcJGH GdCcGOjej(B,s, 2022)
(3jJfGhd gPG GdcJGH OQGSI eYebI ddGSJbdGdjI GdJfXjejI ddeUGfY GdLRGFQjI, eQqckRG Ydi JCKjQgG Ydi YdGbGJ GdYed hGdEfJGL(B. (3jHOC GdcJGH HJbOje NdajI JGQjNjI dSjGSGJ GdJUfjY aj GdLRGFQ, Ke jfJbd Edi JMdjd GdeQGMd GdJfXjejI GdJj eQJ HgG GdeDSSGJ GdYehejI GdUfGYjI(B. (3HYO Pdc, jJYeb GdcJGH aj OQGSI eaghe GdGSJbdGdjI aj Xd GdEUdGMGJ GdGbJUGOjI hGdhVY GdGbJUGOj hGdGLJeGYj NdGd EYGOI GdgjcdI GdGbJUGOjI(B. (3jbOe GdaUd GdNGeS JMdjkdG ejOGfkjG eaUkdG dOQGSI MGdI GdeDSSI GdYehejI GdLRGFQjI ddCfSLI GdUfGYjI aj GdeSjdI, HgOa age GdBKGQ GdYedjI ddGSJbdGdjI GdJfXjejI Ydi eSJhi GdeDSSI(B. (3aj GdfgGjI, jbOe GdcJGH JMdjkdG TGedkG ddfJGFL GdJj Je GdJhUd EdjgG, eSJNdkUG GdOQhS hGdYHQ GdeSJaGOI ef gPg GdOQGSI(B.s
(3GdeQGLY U(B.379s
Keywords: (3GdEOGQI GdJfajPjI (B- (3GdGfJGL (B- (3GdLRGFQs; (3GdeDSSI GdYehejI GdLRGFQjI ddCfSLI GdUfGYjI (B- (3GdeSjdIs